The Impact of Member Personality on Group Performance - Ernst, Kevin; McHugh, Kristie (Journal of Knowledge Management Practice, 2024)
In an increasingly complex world, groups are often formed to solve complex problems on short timelines. This study examines the impact of the personality of the individual group members on the overall group’s performance. Personality is assessed in terms of left vs. right brain dominance and personality type using the NERIS® model. Data is collected from 374 students participating in a Pitch Competition as part of a Principles of Entrepreneurship course. Analysis found that groups with at least one member who had moderate left-brain dominance were more likely to perform better than groups without these types of members. Groups with at least one member who was classified as a diplomat personality type were more likely to perform better than groups without these types of members.
Keywords: knowledge management; personality; group formation; performance